Obtaining Ionospheric Conditions according to Data of Navigation Satellites - Olga Maltseva; Natalia Mozhaeva (International Journal of Antennas and Propagation)
Defining ionospheric conditions, the deviation of the observational value of the total electron content TEC(obs), measured by means of navigation satellites, from a median is a bench mark. According to more than 40 ionospheric stations during April 2014 it is shown that synchronism of change of deviations of TEC and critical frequency foF2 of the ionosphere is kept under quiet and moderate disturbed conditions. This fact allows to use a median of the equivalent slab thickness τ(med) as a reliable calibration factor to calculate foF2 from TEC(obs). The efficiency coefficient of joint use of τ(med) and TEC(obs) changes from 1.5 to 4 with average value 2.2 across the globe. The highest coefficient corresponds to middle latitudes, however the estimations obtained for high- and low-latitude areas indicate possibility to use τ(med) and TEC(obs) in these areas.